Региональное и национальное разнообразие как фактор развития теории Public Administration: постановка проблемы - Паин, Эмиль (Вопросы государственного и муниципального управления, 2015)
The article discusses the problem of the applicability of modern public administration theories and practices outside liberal democracies. The theory and practice are not universal; they do not apply to the conditions of the most numerous type of state in the world, namely nation-states, with «hybrid» political regimes and a mixed system of economic, social and cultural relations. The type of political and socio-economic development of these states cannot be defined in some fields; it is extremely resolute in being temporary and transitional. This is especially true in societies with clan and patron-client relationships, where these prevail at each level of the civil service hierarchy. By using the examples of Kazakhstan and Uzbekistan, the author shows that this type of relationship gives rise to corruption, but also performs a number of important functions in the social sphere, and could sometimes be used as capital modernization by the authorities. Russia, described in the article as a country with ruined social mutual aid traditions, demonstrates that clan relationship traditions continuing in a number of Central Asian countries may cause less damage than full social atomization. The paper is aimed at formulating a hypothesis of the feasibility of convergent approach in public administration theory development for further research. The core idea represents the counter convergence of the theories and the real conditions of governance in various nation-states with hybrid regimes. The article is based on the author’s own research and the public administration department’s student studies, performed under his supervision.